Meningkatkan Kemampuan Critical Thinking Menggunakan Focus Group Discussion Siswa Tahun Pertama Smp Ma’arif Kota Metro - Haikal Haikal (Berkala Ilmiah Pendidikan, 2021)
Critical thinking is needed by every individual to address the problems of life they face. In critical thinking, a person can adjust, adjust, change, or improve his thoughts so that he can act more appropriately. The purpose of this study was to find out how to improve critical thinking skills through focus group discussions. This study uses a qualitative approach. The sample in this study was determined through a sampling technique, namely the purposive sampling technique. The sample in this study were 20 first year students of SMP Maarif in metro city. Data collection techniques in this study used interview techniques and observation techniques. In this study, the data were analyzed using qualitative descriptive analysis. The results obtained from this study are the nature of student zuhud can be realized well where students are able to grow critical thinking skills in understanding adolescent problems.